The Meaning of Pentecost in Early Methodism: Rediscovering John Fletcher as John Wesley's Vindicator and Designated Successor - Wood, Laurence W. (Rowman & Littlefield Publishers, 2002)
John Fletcher's theology of Pentecost is generally unknown today, and this book is the first comprehensive treatise on this subject. His writings were in large part responsible for shaping the theology of early American Methodism, especially his treatise on Christian Perfection, which highlighted a theology of Pentecostal sanctification. Wood recounts the decisive influence Fletcher had on early Methodism, and shows that his writings were able to "control the opinions of the largest and most effective body of evangelical clergymen of the earth." Fletcher's views on the Holy Spirit were also relevant in the ecumenical movement, specifically with reference to the World Council of Churches Commission on Faith and Order held in Lima, Peru, in 1982. This group recommended the introduction of a liturgy of the Spirit in Christian baptism. For students and scholars or general readers interested in Methodist history and theology. Also a resource for pastors-helpful in developing a theology of Pentecost that will preach in a relevant way in the contemporary world.